Clinical characteristics and evolution of 71 neonates born to mothers with COVID-19 at a tertiary center in Brazil (Clinics, 2022)
Introduction: Limited data are available on pregnant women with COVID-19 and their neonates.Objective: This study aimed to describe clinical characteristics and evolution from birth to discharge of a retrospective cohort of 71 neonates, with one set of twins, born to women with COVID-19 diagnosed at the end of pregnancy. The authors included all newborns admitted into a neonatal unit of a tertiary hospital in Brazil, between March 2020 and March 2021, whose unvaccinated mothers had COVID-19 symptoms and RT-PCR (Real-Time Polymerase Chain Reaction) for SARS-CoV-2 positive within fourteen days prior to delivery. Newborns to mothers with COVID-19 symptoms and negative tests for SARS-CoV-2 were excluded.Results: The main route of birth delivery was cesarean, corresponding to 60 pregnant women (84.5%). The foremost indications for cesarean were pregnant with critical disease (24.6%) and acute fetal distress (20.3%). The mean birth weight was 2452 g (865‒3870 g) and the mean gestational age was 345/7 weeks (25‒40 weeks). There were 45 premature newborns (63.3%), of which 21 newborns (29.5%) were less than 32 weeks of gestational age. RT-PCR for SARS-CoV-2 on oropharyngeal swabs was positive in 2 newborns (2.8%) and negative in the other 69 newborns (97.2%). Most newborns (51.4%) needed respiratory support. Therapeutic interventions during hospitalization were inotropic drugs (9.9%), antibiotics (22.8%), parenteral nutrition (26.8%), and phototherapy (46.5%).Conclusion: Maternal COVID-19 diagnosticated close to delivery has an impact on the first days of neonatal life.